Daya Guna Budaya Organisasi dalam Meningkatkan Kinerja Sekolah (Studi di MIS Nurus Salam, Kec. Deli Tua, Kab. Deli Serdang) - Fitri Hayati; Bening Luhur Junani (Journal on Education, 2023)
School as an educational organization produce competent human resources in the era of globalization in all areas of life. Poor academic performance can be seen from the application of cultural content school environmental design, for example poor student numbers or innovative strengths and less teacher creativity. A good school community organizational culture is absolutely necessary form and lead, especially in the application of standards, values and work ethics Attitudes and daily behavior to achieve school goals, produce quality graduates succeed nationally and internationally and face competition. The purpose of the study is to find out: (1) The effectiveness of organizational culture according to norms, values and work ethic in improving school performance at MIS Nurus Salam; (2) Barriers facing the rationalization of organizational culture to increase school success at MIS Nurus Salam; (3) Efforts to rationalize organizational culture to improve school performance at MIS Nurus Salam. The research method used in The preparation of this work is descriptive qualitative. Namely data collection techniques with interviews, observations and documentary studies. The research results show that: (1) About organizational culture Aspects of standards, values and work ethic in improving school performance at MIS Nurus Salam good. This can be seen from the application of norms, values and work ethic that have become behavior and the daily habits of all school members; (2) Obstacles encountered The rationalization of organizational culture can come from within or outside the individual; (3) To improve the organizational culture, investment is made in teacher training and staff and facilities and infrastructure that must be filled.